Chromosome 1p36 Deletion Syndrome: Prenatal Diagnosis, Molecular Cytogenetic Characterization and Fetal Ultrasound Findings - Chih-Ping Chen (Taiwanese Journal of Obstetrics & Gynecology, 2010)
Objective: To present prenatal diagnosis and molecular cytogenetic characterization of de novo partial monosomy 1p (1p36.23→pter) and partial trisomy 20p (20p12.1→pter) associated with ventriculomegaly, ventricular septal defect and midface hypoplasia. Materials, Methods and Results: A 31-year-old, primigravid woman was referred for amniocentesis at 20 gestational weeks because of ventriculomegaly, ventricular septal defect, and midface hypoplasia. Amniocentesis revealed an aberrant derivative chromosome 1, or der(1). Parental karyotypes were normal. Spectral karyotyping analysis revealed that the der(1) contained a segment of chromosome 20 in the distal end of the short arm of chromosome 1. Array comparative genomic hybridization demonstrated an 8.4-Mb distal 1p deletion and a 14-Mb distal 20p duplication. The karyotype was 46,XX,der(1)t(1;20)(p36.23;p12.1)dn. Polymorphic DNA marker analysis determined the paternal origin of the aberrant chromosome. The pregnancy was subsequently terminated. A 462-g malformed female fetus was delivered at 22 gestational weeks with a prominent forehead, midface hypoplasia, a flat nasal bridge, low-set ears, a long philtrum, a pointed chin and micrognathia. Conclusion: Spectral karyotyping, fluorescence in situ hybridization and array comparative genomic hybridization are useful for the prenatal investigation of the nature of a de novo aberrant derivative chromosome. Partial monosomy 1p (1p36.23→pter) and partial trisomy 20p (20p12.1→pter) are associated with ventriculomegaly, ventricular septal defect and midface hypoplasia on prenatal ultrasound. Prenatal diagnosis of ventriculomegaly, congenital heart defects and midface hypoplasia should alert clinicians to chromosome 1p36 deletion syndrome and prompt molecular cytogenetic analysis if necessary.